Halloysite and chitosan oligosaccharide nanocomposite for wound healing. (15th July 2017) - Sandri, Giuseppina; Aguzzi, Carola; Rossi, Silvia; Bonferoni, Maria Cristina; Bruni, Giovanna; Boselli, Cinzia; Cornaglia, Antonia Icaro; Riva, Federica; Viseras, Cesar; Caramella, Carla; Ferrari, Franca
Graphical abstract: Abstract: Halloysite is a natural nanotubular clay mineral (HNTs, Halloysite Nano Tubes) chemically identical to kaolinite and, due to its good biocompatibility, is an attractive nanomaterial for a vast range of biological applications. Chitosan oligosaccharides are homo- or heterooligomers of N-acetylglucosamine and D-glucosamine, that accelerate wound healing by enhancing the functions of inflammatory and repairing cells. The aim of the work was the development of a nanocomposite based on HNTs and chitosan oligosaccharides, to be used as pour powder to enhance healing in the treatment of chronic wounds. A 1:0.05 wt ratio HTNs/chitosan oligosaccharide nanocomposite was obtained by simply stirring the HTNs powder in a 1% w/w aqueous chitosan oligosaccharide solution and was formed by spontaneous ionic interaction resulting in 98.6% w/w HTNs and 1.4% w/w chitosan oligosaccharide composition. Advanced electron microscopy techniques were considered to confirm the structure of the hybrid nanotubes. Both HTNs and HTNs/chitosan oligosaccharide nanocomposite showed good in vitro biocompatibility with normal human dermal fibroblasts up to 300 μg/ml concentration and enhanced in vitro fibroblast motility, promoting both proliferation and migration. The HTNs/chitosan oligosaccharide nanocomposite and the two components separately were tested for healing capacity in a murine (rat) model. HTNs/chitosan oligosaccharide allowed better skin reepithelization and reorganization than HNTs or chitosan oligosaccharide separately. The results suggest to develop the nanocomposite as a medical device for wound healing. Statement of Significance: The present work is focused on the development of halloysite and chitosan oligosaccharide nanocomposite for wound healing. It considers a therapeutic option for difficult to heal skin lesions and burns. The significance of the research considers two fundamental aspects: the first one is related to the development of a self-assembled nanocomposite, formed by spontaneous ionic interaction, while the second one is related to the possibility to find an effective treatment for cutaneous non healing lesions. The characterization of this hybrid system involves a multidisciplinary approach considering integrated techniques of solid state investigation and advanced electron microscopies, and in vitro/in vivo models to understand biocompatibility and proliferation properties (enhancement of in vitro fibroblast motility, proliferation and migration, and of in vivo burn healing), to understand safety and effectiveness of the developed nanocomposite.